2014
DOI: 10.1016/j.stemcr.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lapse Analysis of Human Embryonic Stem Cells Reveals Multiple Bottlenecks Restricting Colony Formation and Their Relief upon Culture Adaptation

Abstract: SummaryUsing time-lapse imaging, we have identified a series of bottlenecks that restrict growth of early-passage human embryonic stem cells (hESCs) and that are relieved by karyotypically abnormal variants that are selected by prolonged culture. Only a minority of karyotypically normal cells divided after plating, and these were mainly cells in the later stages of cell cycle at the time of plating. Furthermore, the daughter cells showed a continued pattern of cell death after division, so that few formed long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 27 publications
(31 reference statements)
4
92
0
Order By: Relevance
“…This overestimation of the number of abnormal cells may be due to a difference in cell-cycle time between normal and variant cells. Indeed, we have previously reported a faster cycling time of aneuploid cells compared with their diploid counterparts (Barbaric et al., 2014). As karyotyping relies on cells arrested in metaphase, a different proliferative activity of cells within a mosaic population may bias the analysis toward the more proliferative cells (Gohring et al., 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This overestimation of the number of abnormal cells may be due to a difference in cell-cycle time between normal and variant cells. Indeed, we have previously reported a faster cycling time of aneuploid cells compared with their diploid counterparts (Barbaric et al., 2014). As karyotyping relies on cells arrested in metaphase, a different proliferative activity of cells within a mosaic population may bias the analysis toward the more proliferative cells (Gohring et al., 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Some of the variant cells with common genetic changes show signs of neoplastic progression (Werbowetski-Ogilvie et al., 2009), including reduced apoptosis (Avery et al., 2013, Yang et al., 2008), growth-factor independence (Werbowetski-Ogilvie et al., 2009) and higher cloning efficiency (Barbaric et al., 2014, Enver et al., 2005). Genetic changes can also affect the differentiation propensity of hPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been clearly demonstrated in single-celled organisms (Rancati et al 2008, Selmecki et al 2009, Pavelka et al 2010, Yona et al 2012, Chang et al 2013, however, demonstrating this in human cells has been more challenging. There is evidence that aneuploid human cells, although generally appearing less fit than their euploid counterparts under 'standard' conditions (Williams et al 2008, Thompson & Compton 2010 display advantages under selective conditions (Rutledge et al 2016) and that aneuploidy of pluripotent stem cells promotes their efficient adaptation to culture conditions (Barbaric et al 2014, Na et al 2014. Further, aneuploidy in murine liver cells promotes adaptation to chronic liver injury (Duncan et al 2012).…”
Section: Cin: a Clinical Problemmentioning
confidence: 99%
“…A previous report demonstrated that the mitotic activation of actomyosin sometimes stimulated cell death, mirroring the dissociation-induced phenotype (Barbaric et al., 2014). Considering that cellular adhesiveness is dynamically rearranged during mitosis, spontaneous failures in the adhesion-mediated control of ABR activity could occur upon mitosis.…”
Section: Discussionmentioning
confidence: 86%